2001
DOI: 10.1095/biolreprod64.2.619
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin Inhibits the Contraction of Cultured Rat Testicular Peritubular Myoid Cells Induced by Endothelin-11

Abstract: The present study documents that adrenomedullin (AM), a vasoactive peptide originally identified in pheochromocytoma tissue and present in the testis, in vitro affects the function of testicular peritubular myoid cells (TPMC), a contractile cell type located in the seminiferous tubule wall. AM stimulated cAMP production by cultured TPMC taken from 16-day-old rats, and this effect was completely inhibited by the AM antagonist AM-(22-52) and partially by the CGRP (calcitonin gene-related peptide) antagonist CGRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…The discrepancy of the cell types expressing ADM may be due to species differences. ADM may be one of the local factors controlling the contraction of seminiferous tubules as ADM is able to antagonize EDN1-induced contraction of testicular peritubular myoid cells [19]. In the present study, we found that ADM may regulate steroidogenesis as ADM significantly reduced hCG-stimulated testosterone release by acting on its specific receptors, an inhibitory effect that was abolished by ADM .…”
supporting
confidence: 59%
See 1 more Smart Citation
“…The discrepancy of the cell types expressing ADM may be due to species differences. ADM may be one of the local factors controlling the contraction of seminiferous tubules as ADM is able to antagonize EDN1-induced contraction of testicular peritubular myoid cells [19]. In the present study, we found that ADM may regulate steroidogenesis as ADM significantly reduced hCG-stimulated testosterone release by acting on its specific receptors, an inhibitory effect that was abolished by ADM .…”
supporting
confidence: 59%
“…Recent studies have also shown the gene expression or peptide of Adm in reproductive organs such as the ovary [13,14], uterus [13,15], testis [12], prostate [16,17], and epididymis [18]. In addition, ADM inhibits endothelin 1 (EDN1)-induced contraction of seminiferous tubules [19], in which ADM receptors are found in testicular peritubular myoid cells [20]. These findings suggest that ADM may play a role in the male reproductive system.…”
Section: Introductionmentioning
confidence: 96%
“…This effect was mostly mediated by the ADM receptor. These opposite effects of ADM and endothelin (ET) on muscle contraction have already been reported in the vasculature (Stangl et al 2001) and in the testis (Santiemma et al 2001). Endothelin was a 21 amino acid vasocontricting peptides produced primarily in the endothelium and plays a key role in vascular homeostasis.…”
Section: Discussionmentioning
confidence: 96%
“…Our in vivo studies show that PM-AR Ϫ/y mice might have some defects in contractility, thus resulting in decreased sperm output. Earlier studies demonstrated that ET-1 and AM are two balancing factors that control PM cell contraction (35)(36)(37)(38)(39). It is possible that androgen͞AR may go through the modulation of ET-1 and AM (Fig.…”
Section: Pm Cells' Physiological Roles Contributing To Contractility mentioning
confidence: 97%